FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN KECELAKAAN KERJA (Studi Pada Tenaga Kerja Bagian Produksi PT. Arto Metal Internasional Sidoarjo) - Havilia Ayu Haznany; Winarko . (Poltekkes Kemenkes Surabaya, 2013)
PT Arto Metal International is one of the metal components manufacturers, where theproduction processes are using machinaries which its operations may lead to accidents. One ofthe effects that can be caused by the production machines might happen if workers are notcareful, they might got pinched by plong engine, etched plates and exposed debris grams.Therefore, this study aims to determine the factors associated with the incidence of workplaceaccidents in this company.The methods used in this study were analytical methods, because this researchexamined the relationship between 2 (two) variables. Based on its times, this study wascategorized as cross-sectional study, due to variables such as risk factors and effect factorswere observed at the same time. Sampling technique was done by simple random sampling,and analysis was used to determine the relationship between 2 (two) variables using Chi Square.The results showed that employees injured at workplace as much as 94.3%. Theresults of analysis of Chi - Square showed that there were four variables significantlyassociated with the incidence of workplace accidents, they were the use of PPD to theincidence of occupational injuries (p value = 0.025), the level of knowledge to the incidence ofoccupational injuries (p value = 0.047), the ages to the incidence of occupational injuries (pvalue 0.025) and the length of services to the incidence of occupational injuries (p value0.005).Therefore, it is suggested that the company perform incident controlling actionswhether technically, administratively as well as adding a number of Personal ProtectiveDevices (PPD) for workers so that all workers can use it while working.Keywords: Workplace Accident, Personal Protective Devices